A tunable deep eutectic solvent-based processing for valorization of chestnut wood fiber as a source of ellagic acid and lignin. Issue 3 (June 2022) - Moccia, Federica; Gallucci, Noemi; Giovando, Samuele; Zuorro, Antonio; Lavecchia, Roberto; D'Errico, Gerardino; Panzella, Lucia; Napolitano, Alessandra
Abstract: Three different deep eutectic solvent (DES)-based extraction procedures were rationally designed and optimized for the recovery of antioxidants from chestnut wood fiber (CWF), a clean and largely available solid waste of the tannin industry. First, a mild protocol was developed using a choline chloride (ChCl)/tartaric acid DES at 50 °C, for 90 min. Ellagic acid (EA) was identified as the only low molecular weight phenolic component of the extract. In other experiments, harsher conditions were explored involving treatment of CWF with ChCl-based DESs at 120 °C for 8 h, which afforded a solid sample characterized by high phenolic content (up to 1.0 mg of gallic acid equivalents/mg of sample) and antioxidant properties (EC50 <0.025 mg/mL in the 2, 2-diphenyl-1-picrylhydrazyl assay), and containing guaiacyl-syringyl lignin along with EA. Based on these results, a sequential two-step DES-based treatment of CWF was eventually designed, allowing to selectively obtain both an EA-enriched and an EA-free, lignin-enriched sample, with an overall 50% w/w of the starting CWF dissolved. In particular, a 2.3% w/w yield of EA was achieved, which is significantly higher than those reported in the case of DES-based processing of other agricultural wastes. The proposed tunable, straightforward, and eco-friendly approach may allow to fully exploit CWF as a green, cheap, and easily accessible source of high-value products. Graphical Abstract: ga1 Highlights: Chestnut wood fiber (CWF) can be exploited as a clean source of antioxidants. Selective deep eutectic solvent (DES)-based extraction protocols were developed. Choline chloride (ChCl)-tartaric acid DES afforded high yields of ellagic acid. Subsequent treatment of CWF with ChCl-lactic acid DES led to a lignin-rich extract. All the extracts exhibited a high phenol content and potent antioxidant properties.